AS FESTAS DE SANTO E SEUS SUJEITOS HISTÓRICOS: memórias e experiências dos itaiacocanos da Roça Velha (1960 – 2014) - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2016)
This dissertation aims to discuss the ways in which rural workers from Roça Velha’s community, in Itaiacoca’s district (Ponta Grossa – PR) experienced the Feast of the Saints, commom pratices in the district until mid- 1990’s. This issue attempt to highlight the ways in which these individual recall and experience the festivities today, from his current conditions, including of migrants from countryside. In order to this, the research contextualizes the district and rural community, in its transformations and permanencies, during the 1960s and 2014. It also present the festivities, in its dynamics and rituals, as well as the relation of the Catholic Church with these practices. To finally discuss how among many processes this individuals experienced the feasts and what roles have in the building of their identities.
Keywords: Roça Velha; Festas de Santo; memórias; identidades; Roça Velha; Feast of the Saints; memories; identities; CNPQ::CIENCIAS HUMANAS::HISTORIA